2019
DOI: 10.3390/ijerph16203986
|View full text |Cite
|
Sign up to set email alerts
|

Natural Landscape, Infrastructure, and Health: The Physical Activity Implications of Urban Green Space Composition among the Elderly

Abstract: Urban green spaces (UGS) have been linked with a series of benefits for the environment, and for the physical health and well-being of urban residents. This is of great importance in the context of the aging of modern societies. However, UGS have different forms and characteristics that can determine their utilization. Common elements in UGS such as the type of vegetation and the type of surface are surprisingly understudied in regard to their relationship with the type of activity undertaken in UGS. This pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 59 publications
0
34
0
Order By: Relevance
“…This would be a similar approach to that suggested for children and schools [43]. On the other hand, and considering the importance of paved surfaces for seniors walking activity [33], efforts aimed at guaranteeing certain levels of walking activity among seniors in urban and high walkable environments should be focusing on safety issues. This would be particularly relevant under rainy conditions, for instance, by investing in street design elements such as sidewalks or curb ramps, that are relevant in seniors' safety [39,44,45], and therefore contributing to reducing the risk of falling and the risk of accidents under such circumstances.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This would be a similar approach to that suggested for children and schools [43]. On the other hand, and considering the importance of paved surfaces for seniors walking activity [33], efforts aimed at guaranteeing certain levels of walking activity among seniors in urban and high walkable environments should be focusing on safety issues. This would be particularly relevant under rainy conditions, for instance, by investing in street design elements such as sidewalks or curb ramps, that are relevant in seniors' safety [39,44,45], and therefore contributing to reducing the risk of falling and the risk of accidents under such circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…To examine associations between weather variables and walkability with daily walking levels, we first conducted descriptive statistics followed by multilevel linear mixed effects models with user identification number as the random effect, as conducted in similar studies [33]. First, we applied non-parametric tests (the Mann-Whitney U test for binary variables and the Kruskal-Wallis test for categorical variables with more than three categories) to evaluate the association between each independent variable and the outcome, daily walking minutes.…”
Section: Measures and Analysismentioning
confidence: 99%
“…Additionally, a recent study showed that among older adults during their time spent within urban green spaces (parks and gardens) sedentary behaviors were more common than physical activities [50]. This indicates that built environments are complex and dynamic systems, and the modelling of the combinations of multiple environmental variables and indices, is needed, as previously highlighted in Sallis et al [51].…”
Section: Neighborhood Walkability and Physical Activitymentioning
confidence: 99%
“…The recognition of the role of BE in PA has grown. Green space, one of the most studied BE characteristics, was found to be positively associated with PA in general [ 7 , 8 , 9 , 10 ]. Other BE characteristics, such as residential density, public transport density and number of PA-related facilities, are also important to the promotion of PA [ 11 , 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%